Finite Element Analysis of Shear Performance for Reinforced Concrete T-Beams by Polymer Bars Strengthened with Carbon Fiber Using Embedded Through Section Technique (Journal of Engineering, 2024)
The purpose of this research presents the research results obtained from a numerical simulation using the ABAQUS/CAE version 2019 finite element software. This study tested the shear behavior of T-beams made of reinforced concrete (RC). The structure is reinforced with a carbon fiber reinforced polymer (CFRP) bar embedded through a section (ETS). The numerical validation approach implicated using numerical analysis on the experimental data collected from twelve reinforced concrete (RC) T-beams divide into two groups each group include reference beam, the field of numerical analysis was expanded to encompass the examination of many aspects, such as the impact of the diameter of CFRP bars. The main objective of this project is to create a computational model that accurately transcribes the complex nonlinear properties inherent in beams. This work conducts a comparative investigation of computational and experimental models, with a specific focus on their load-deflection features and cracking patterns. The study found that the average ratio of ultimate load to deflections in numerical model simulations for beams was 1.011, whereas in experimental testing it was 0.928. The research findings establish a clear correlation between the diameter of CFRP bars and the stiffness of a beam, assuming a constant angle of inclination and spacing.